Effect of water aging of adherend composite on repair bond strength of nanofilled composites - Daiki Nagano (2018)
© Quintessenz. Purpose: To evaluate the effect of water aging of adherend composite on repair bond strength to nanofilled composites with specific fillers using different bonding agents. Materials and Methods: Three nanofilled composites - Beautifil II with S-PRG filler (BE) / Filtek Supreme ultra with nanocluster filler (SP) / Estelite Σ Quick (ES) - and one microhybrid composite, Clearfil APX (AP), were used in this study. The composite disks were immersed in water for different durations (immediate, 1 week, 2 weeks or 1 month), and then the polished surfaces were treated with one of three bonding agents - no treatment (control), application of Clearfil SE One (SE), application of Clearfil SE One plus Clearfil Porcelain Bond Activator (PB) - then filled with a repair composite. The bonded composite disks were subjected to the microshear bond strength (μSBS) test. Additionally, water sorption (Wsp) and solubility (Wsl) of the resin composite were measured. The μSBS data were was statistically analyzed using a three-way ANOVA and t-test with Bonferroni correction for multiple comparisons. Results: Water aging of adherend composite affected the repair bond strength (p < 0.05). For BE, SP, and ES, application of an adhesive agent improved repair bond strengths to water-aged composites (p < 0.05), but adding a silane coupling agent could not (p > 0.05). For AP, the μSBS significantly increased, with control group < SE group < PB group (p < 0.05). Conclusion: Microhybrid composite was a more suitable material for composite repair than nanofilled composite, due to adhesion to exposed, larger silica fillers. S-PRG filler and nanocluster filler in the nanofilled composites played a slight role in improving their repair bonding performances with the bonding agents tested.